Vascular Hamartoma in the Uterus of a Female Sprague-Dawley Rat with an Episode of Vaginal Bleeding. (October 2013) - Shirota, Mariko; Kawashima, Jun; Nakamura, Tomohiro; Ogawa, Yuko; Kamiie, Junichi; Shirota, Kinji
An annular, reddened lesion with mild serosal hemorrhage and no tumorous mass formation was detected in the right uterine horn of a 37-week-old female Sprague-Dawley rat that had postpubertal vaginal bleeding. Histological examination revealed prominent proliferation of the endometrium, which occupied the uterine lumen. There were numerous aberrant vascular spaces filled with erythrocytes, proliferation of stromal cells, and inflammatory infiltrates including hemosiderin-laden macrophages in the endometrium. These vasculatures extended into the myometrium, and in a transverse section of the lesion, they were mostly distributed throughout the circumference of the uterus. They were irregular in shape and interconnected, forming a large vascular sinus and anastomosing reticular channels. In the area with serosal hemorrhage, the muscular layer covering the large irregular vascular space had undergone degeneration and necrosis. The lining cells of the vasculatures were often plump, and they protruded into the lumen and were arranged in a tombstone or hobnail manner. Immunostaining revealed that these cells were positive for von Willebrand factor and CD34. The aberrant vasculatures were not accompanied by pericytes or muscular layer, although a discontinuous muscular wall was present around some of them. From these results, the uterine lesion was diagnosed as a vascular hamartoma.